2008
DOI: 10.1016/j.ejphar.2008.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Role of α2-adrenoceptors in enhancement of antinociceptive effect in diabetic mice

Abstract: The present studies investigated behavioral and neurochemical aspects of the noradrenergic and serotonergic nervous systems in streptozotocin-induced diabetic mice.We previously reported that intrathecal (i.t.) injection of norepinephrine significantly potentiated antinociception in diabetic mice compared to that in non-diabetic mice, and that antinociception due to norepinephrine injection was completely abolished by pretreatment with yohimbine, an α 2 -adrenoceptor antagonist. The present studies demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The mechanisms underlying increased ␣ 2 -adrenoceptor activity in the spinal cord in diabetic neuropathy are not fully known. It has been reported that diabetic neuropathy reduces the norepinephrine release and causes a compensatory up-regulation of the ␣ 2 -adrenoceptor in the spinal cord (Omiya et al, 2008). Nevertheless, because the endogenous ligand for ␣ 2 -adrenoceptors may be reduced in diabetic rats, this could explain why the baseline glutamate release at the spinal level is still elevated in diabetic rats.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The mechanisms underlying increased ␣ 2 -adrenoceptor activity in the spinal cord in diabetic neuropathy are not fully known. It has been reported that diabetic neuropathy reduces the norepinephrine release and causes a compensatory up-regulation of the ␣ 2 -adrenoceptor in the spinal cord (Omiya et al, 2008). Nevertheless, because the endogenous ligand for ␣ 2 -adrenoceptors may be reduced in diabetic rats, this could explain why the baseline glutamate release at the spinal level is still elevated in diabetic rats.…”
Section: Discussionmentioning
confidence: 54%
“…Many experimental studies have demonstrated that intrathecal or systemic administration of ␣ 2 -adrenoceptor agonists can produce a potent analgesic effect in neuropathic pain caused by traumatic nerve injury and diabetic neuropathy (Courteix et al, 1994;Yaksh et al, 1995;Calcutt and Chaplan, 1997;Buerkle and Yaksh, 1998;Pan et al, 1999;Omiya et al, 2008). In addition, clinical studies have shown that spinally administered ␣ 2 -adrenoceptor agonists reduce the intractable neuropathic pain caused by nerve injury and cancer (Rauck et al, 1993;Hassenbusch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants with dual inhibition of 5-HT and NA are more effective than selective compounds in the treatment of NP in rats [21,22]. Moreover, it was also demonstrated that intrathecal injection of NA or 5-HT produced a strong antinociceptive effect in STZ-treated rodents [23][24][25]. The antinociceptive effects of VFX depend on the administered doses.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of tramadol on neuropathic pain is considered to be at least partly due to its interaction with presynaptic and postsynaptic a 2 -ARs located on the central terminals of primary nociceptive afferents and the spinal dorsal horn neurons, respectively (35 -37). The analgesic potency of tramadol (26), as well as a 2 -AR agonists (38,39), is enhanced in neuropathic pain, probably due to the increased activity of presynaptic and postsynaptic a 2 -ARs (40). Thus, the present results do not exclude the possibility that the analgesic effect of tramadol on neuropathic pain is partly mediated through a 2 -ARs.…”
Section: Discussionmentioning
confidence: 99%